Social robots and L2 teaching for children: a preliminary study on the embodiment of gestures - Silvia Gasparini (Firenze University Press, 2019)
Experimental research confirms that using social robots with pre-school children as tutors for their learning has important positive effects in terms of children's learning and emotional involvement. In particular, the use of social robots for language learning (L1 and L2) leads to more learned words and a better memory of them. However, many technological limitations prevent from fully implementing the concept of embodiment, a distinctive feature of robotic technology compared to other computer-based technologies, and especially of gestures. In order to contribute to solve the problem, in a preliminary psychological test with Italian children learning English as L2, it was shown that appropriate modifications of the learning environment combined with a more limited use of gestures allow to achieve better results in terms of learning than a larger use of gestures in a less structured environment. If experimentally verified, these results would suggest the development of learning architectures which offer more affordances with respect to the task at hand, while implementing more limited forms of embodiment that are in line with current technological limitations.   Robot sociali e insegnamento di L2 ai bambini: uno studio preliminare sull'embodiment della gestualità Le ricerche sperimentali confermano che l'utilizzo di robot sociali in funzione di tutor per l'apprendimento di bambini nella fascia di età prescolare ha importanti effetti positivi in termini di apprendimento e di coinvolgimento emotivo dei bambini. In particolare, l'uso di robot in supporto all'apprendimento linguistico (L1 e L2) si traduce in un numero maggiore di parole apprese e in un migliore ricordo delle stesse. Numerosi limitazioni tecnologiche impediscono tuttavia la piena realizzazione nei robot sociali del concetto di embodiment, in particolare per quanto riguarda la gestualità. Proprio per contribuire a dare una soluzione al problema, in una prova psicologica preliminare con bambini italiani che apprendono la lingua inglese come L2 si dimostra che in un ambiente di apprendimento opportunamente strutturato una gestualità più limitata permette di conseguire migliori risultati di apprendimento e ricordo delle parole apprese rispetto a un uso maggiore della gestualità in un ambiente meno organizzato. Se sperimentalmente verificati, tali risultati indirizzerebbero verso lo sviluppo di architetture dell'ambiente di apprendimento più ricche di affordance rispetto al compito che consentano conseguentemente di implementare forme di embodiment più limitate in linea con le limitazioni tecnologiche attuali.